A photovoltaic roof integrated building structure with cooling, heat insulation, flame retardation and power generation synergistic functions

CN122812404APending Publication Date: 2026-09-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610859573.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

[0003]光伏高温降效:光伏组件工作过程中会持续产生热量,加之夏季室外高温辐射,组件温度大幅升高(可达60~80℃),光伏光电转换效率随温度上升显著下降(每升高1℃,效率下降0.4%~0.5%),发电效能损耗严重

Benefits of technology

[0052]1.功能集成度高:单一水凝胶贴片同时实现光伏降温、建筑隔热、防火阻燃三大功能,替代传统的多层复杂构造,结构精简。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122812404A_ABST
    Figure CN122812404A_ABST
Patent Text Reader

Abstract

The application discloses a photovoltaic roof integrated building structure with cooling, heat insulation, flame retardation and power generation synergistic functions, and belongs to the technical field of photovoltaic building integration and building energy saving. The structure comprises a building roof base, an encapsulated phase change material hydrogel functional patch and a photovoltaic module; the patch is arranged between the building roof base and the photovoltaic module, and all side surfaces exposed to the environment are provided with a waterproof encapsulation layer. The patch is composed of a fixed material and a multi-network skeleton, and a composition comprising the following components is formed by chemical cross-linking: inorganic hydrated salt phase change material, self-adhesive material, polymer monomer or polymer skeleton, crystallization nucleating agent, cross-linking agent and water. Under the fixed material collocation, the patch can spontaneously crystallize and produce a slight volume expansion below the crystallization temperature of the material, rigidly interlock with the contact surface of the building roof base and the photovoltaic module, and enhance the adhesion; the multi-network skeleton promotes the acquisition of durable and stable mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of building-integrated photovoltaics (BIPV) technology, building energy conservation and new energy utilization, and specifically relates to a photovoltaic roof integrated building structure with a phase change material hydrogel functional layer. Background Technology

[0002] With the rapid development of distributed photovoltaic power generation and the green building industry, photovoltaic rooftops have gained widespread application due to their advantages of on-site power generation and high space utilization. However, existing conventional photovoltaic rooftops mostly involve directly installing photovoltaic modules on the building's roof surface, which has several technical drawbacks:

[0003] Photovoltaic efficiency degradation due to high temperature: Photovoltaic modules continuously generate heat during operation. Combined with high outdoor temperature radiation in summer, the module temperature rises significantly (up to 60-80℃). The photovoltaic conversion efficiency decreases significantly with increasing temperature (efficiency decreases by 0.4%-0.5% for every 1℃ increase), resulting in severe power generation efficiency loss.

[0004] Increased heat consumption due to roof heat transfer: The photovoltaic modules are closely attached to the roof base, and the heat is directly conducted to the interior of the building, which leads to an increase in the indoor temperature of the house, an increase in the building's cooling energy consumption, and poor heat insulation and cooling effect.

[0005] Significant fire hazards: Photovoltaic modules contain flammable materials such as circuits and encapsulation films. Long-term outdoor use poses risks of electrical fires, hot spots, and high-temperature ignition. Existing roof structures lack dedicated flame-retardant protection designs, making it impossible to guarantee building fire safety.

[0006] Existing technologies add insulation layers (such as polystyrene boards and rock wool) or heat dissipation layers (such as metal fins) between photovoltaic modules and the roof, but these solutions have limited functionality and complex structures. Some solutions use phase change materials for thermal management, but existing phase change materials generally suffer from problems such as high thermal conductivity, poor flame retardancy, easy leakage, and poor compatibility with photovoltaic roofs, making it difficult to simultaneously meet the three core requirements of photovoltaic cooling, building insulation, and fire safety.

[0007] Current technologies treat all photovoltaic cells the same, ignoring the distinctly different thermophysical properties of different cell types (such as highly thermally conductive crystalline silicon versus ultra-low thermally conductive perovskite). Perovskite cells, in particular, are often considered to have extremely low thermal conductivity, a factor detrimental to heat dissipation, and current technologies have never considered how to utilize this characteristic. Recent research has explored the application of phase change materials in photovoltaic heat dissipation, but existing solutions cannot block heat conduction into building interiors, lacking insulation and cooling effects, and failing to fully exploit the potential adhesive properties of hydrogels. Therefore, developing a simple, multi-functional integrated photovoltaic rooftop building structure has become a pressing technical challenge in this field. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides an integrated photovoltaic roof building structure that combines cooling, heat insulation, flame retardancy, and photovoltaic efficiency enhancement. It integrates photovoltaic modules, encapsulated phase change material hydrogel patches, and building roof design. By utilizing the comprehensive characteristics of high latent heat, low thermal conductivity, and high flame retardancy of phase change material hydrogel, it simultaneously achieves temperature control and efficiency enhancement of photovoltaic modules, heat insulation and cooling of building roof, and fire resistance and flame retardancy of the overall structure, simplifying building construction and reducing construction and maintenance costs.

[0009] The technical solution of the present invention:

[0010] A photovoltaic roof integrated building structure that combines cooling, heat insulation, flame retardancy, and power generation efficiency enhancement functions is characterized by:

[0011] The photovoltaic roof integrated building structure includes a building roof substrate, encapsulated phase change material hydrogel functional patches, and photovoltaic modules;

[0012] The encapsulated phase change material hydrogel functional patch is sandwiched between the building roof substrate and the photovoltaic module, with the three being stacked and fixed from top to bottom. All side surfaces of the encapsulated phase change material hydrogel functional patch exposed to the environment are provided with a waterproof vapor-sealing layer to prevent internal moisture evaporation from causing phase change and failure.

[0013] The encapsulated phase change material hydrogel functional patch is composed of a multi-network framework constructed using a fixed material combination. The composition includes the following components, formed through chemical cross-linking: inorganic hydrated salt phase change material, self-adhesive material, polymer monomers or polymer framework, crystallizing nucleating agent, cross-linking agent, and water. With this fixed material combination, the encapsulated phase change material hydrogel functional patch can spontaneously crystallize below the material's crystallization temperature and undergo micro-volume expansion, forming a rigid interlock with the building roof substrate and photovoltaic module contact surface, enhancing adhesion; the multi-network framework promotes durable and stable mechanical properties.

[0014] Furthermore, the encapsulated phase change material hydrogel functional patch has the following basic characteristics:

[0015] (a) High latent heat: latent heat of phase transition Preferred The phase transition temperature range is 18–60℃, preferably 18–38℃;

[0016] (b) Low thermal conductivity: thermal conductivity at room temperature ;

[0017] (c) High flame retardancy: The flame retardancy rating reaches class.

[0018] Furthermore, it absorbs heat from the photovoltaic module during the day to undergo a phase change and melt to reduce the temperature of the photovoltaic module, and releases heat at night to crystallize and recover, while possessing self-adhesive properties and the ability to block heat conduction and flame spread throughout the process.

[0019] Furthermore, the building roof base can be any one of concrete roof, asphalt roof, waterproof membrane roof, wood structure roof, insulation board roof, or steel structure roof (such as color steel roof).

[0020] Furthermore, the photovoltaic module is any one of crystalline silicon photovoltaic panels, thin-film photovoltaic panels, double-glass photovoltaic panels, flexible photovoltaic panels, and other novel photovoltaic modules.

[0021] Furthermore, the crystalline silicon in the crystalline silicon photovoltaic panel has high thermal conductivity ( The solar thermal energy is rapidly absorbed and conducted from the front to the back of the crystalline silicon photovoltaic panel. The temperature difference between the upper and lower surfaces of the crystalline silicon photovoltaic panel is less than 1°C. The encapsulated phase change material hydrogel functional patch absorbs and stores heat, and acts only as a passive cooling layer to reduce the operating temperature of the crystalline silicon photovoltaic panel. The operating temperature drops from 50.3°C to 28.2°C, a decrease of 14.9°C, and the photoelectric conversion efficiency increases from 13.65% to 15.11% (a relative increase of 10%).

[0022] Furthermore, in the perovskite solar cells of the aforementioned thin-film photovoltaic panel, the perovskite material has an ultra-low thermal conductivity ( Without damaging the perovskite solar cell structure, a vertical temperature gradient is actively constructed and maintained through localized cooling of the back surface. This temperature gradient is converted into a thermoelectric field, which, in conjunction with the photoelectric field, leverages the perovskite's low thermal conductivity. Under illumination, the front side (light-receiving side) of the perovskite solar cell generates Joule heating, becoming the hot end, while the back side absorbs heat due to the encapsulated hydrogel functional patch, becoming the cold end. Because the perovskite layer has extremely poor thermal conductivity, this temperature difference cannot be homogenized through heat conduction, thus establishing a vertical temperature gradient along the device's thickness. This vertical temperature gradient drives carrier migration, generating a thermoelectric potential that, in series with the photoelectric field, enhances the photovoltaic-thermoelectric coupling. This not only achieves cooling but also increases the photoelectric conversion efficiency from 20.22% to 22.89%, improves the open-circuit voltage by 0.278V, and increases the short-circuit current density. .

[0023] Furthermore, the encapsulated phase change material hydrogel functional patch is a flexible, monolithic or modular partitioned design, with each photovoltaic module corresponding to a single encapsulated phase change material hydrogel functional patch, facilitating later inspection, replacement, and maintenance; the patch thickness is... The selection should be based on the climate conditions of the building's location, the roof orientation, and the power of the photovoltaic modules.

[0024] Furthermore, the preparation method of the encapsulated phase change material hydrogel functional patch includes the following steps:

[0025] (1) Inorganic hydrated salt phase change material, self-adhesive material, various polymer monomers or polymer skeletons, crosslinking agent, crystallizing nucleating agent, initiator and water are mixed in proportion and injected into a mold. The shape can be adjusted arbitrarily according to the mold and can be prepared on a large scale.

[0026] (2) The polymer monomers and crosslinking agents form a chemically crosslinked multi-network structure by ultraviolet light irradiation or thermal polymerization;

[0027] (3) Demolding to obtain a self-adhesive phase change material hydrogel functional patch;

[0028] (4) Add a waterproof vapor encapsulation layer to all side surfaces of the phase change material hydrogel functional patch exposed to the environment, directly attach the encapsulated phase change material hydrogel functional patch to the upper surface of the building roof substrate, and then attach the photovoltaic module. Let it stand for 2-10 hours in an environment lower than the crystallization temperature of the encapsulated phase change material hydrogel functional patch, or by local cooling, so that the encapsulated phase change material hydrogel functional patch spontaneously crystallizes and forms a rigid interlock with the upper and lower surfaces.

[0029] Furthermore, the encapsulated phase change material hydrogel functional patch, in its molten state, is transparent and possesses self-adhesion and strong adhesion. Shear deformation It can perfectly fit photovoltaic modules; in its crystalline state, it is milky white, and the encapsulated phase change material hydrogel functional patch transforms into a rigid material with increased adhesion strength. The micro-expansion of volume during crystallization forms a mechanical interlock with the micro-rough structure of photovoltaic modules and building roof substrates; the presence state of the encapsulated phase change material hydrogel functional patch can also be determined by color change. After more than 500 melting-crystallization cycles, the latent heat retention rate of phase change is ≥99%, with no leakage.

[0030] Furthermore, the inorganic hydrated salt phase change material is selected from any one or more of sodium sulfate decahydrate, sodium carbonate decahydrate, disodium hydrogen phosphate dodecahydrate, calcium chloride hexahydrate, zinc nitrate hexahydrate, sodium thiosulfate pentahydrate, and sodium acetate trihydrate, and the phase change temperature can also be adjusted to the range of 18-38℃ through eutectic treatment.

[0031] Furthermore, the nucleating agent is selected from any one or more of borax, cesium chloride hexahydrate, strontium chloride hexahydrate, sodium metasilicate nonahydrate, nano silica, nano alumina, and graphene quantum dots, and the amount of nucleating agent added is 0.01% to 15% (preferably 0.1% to 10%) of the mass of the inorganic hydrated salt phase change material.

[0032] Furthermore, the polymer backbone is a network backbone of chemically cross-linked polymer monomers; the polymer backbone is selected from any one or more of polyacrylamide, polyacrylic acid, sodium polyacrylate, polymethacrylic acid, sodium polymethacrylate, polyN-isopropylacrylamide, poly2-acrylamido-2-methylpropanesulfonic acid, polyvinylpyrrolidone, polyvinyl alcohol, polydimethyldiallylammonium chloride, and sodium alginate; the amount of polymer monomer added is 0.5% to 10% (preferably 1% to 5%) of the mass of the inorganic hydrated salt phase change material.

[0033] Furthermore, the self-adhesive material is selected from any one or more of the following: dopamine methacrylamide, gelatin, gallic acid, protocatechuic aldehyde, tannic acid, poly-N-isopropylacrylamide, hyaluronic acid, chitosan and its derivatives, corn starch, and carboxybetaine; the amount of self-adhesive material added is 0.01% to 20% (preferably 0.1% to 15%) of the mass of the inorganic hydrated salt phase change material.

[0034] Further, the crosslinking agent is selected from any one or more of N,N'-methylenebisacrylamide, dimethyl diallyl ammonium chloride, and glutaraldehyde; the amount of crosslinking agent added is 0.0001% to 0.01% (preferably 0.0005% to 0.005%) of the mass of the inorganic hydrated salt phase change material.

[0035] Further, the initiator is selected from any one or more of α-ketoglutaric acid, ammonium persulfate, potassium persulfate, and azobisisobutyramidine hydrochloride; the amount of initiator added is 0.0001% to 0.01% (preferably 0.0005% to 0.005%) of the mass of the inorganic hydrated salt phase change material.

[0036] Three core properties of phase change material hydrogel functional patches

[0037] (1) High latent heat characteristics Preferred )

[0038] The patch uses a composite phase change material hydrogel substrate with a latent heat of phase change ≥140J / g. The phase change occurs within the phase change temperature range of 18–50℃ (preferably 18–38℃), absorbing radiant heat from the photovoltaic module and outdoor solar radiation. This phase change heat storage suppresses the temperature rise of the photovoltaic module and stabilizes its operating temperature. Actual measurements show that the operating temperature of the photovoltaic module can be reduced by 10–20℃, and the power generation efficiency can be relatively improved by 8%–12%.

[0039] (2) Low thermal conductivity )

[0040] Hydrogels contain a large amount of water and polymer chains, exhibiting strong phonon scattering and a thermal conductivity much lower than that of traditional phase change materials (typically). ). Thermal conductivity of surface mount at room temperature (By optimizing the polymer network and water content, the thermal conductivity can be further reduced), forming a thermal barrier layer: on the one hand, it blocks the conduction of outdoor high temperatures and waste heat from photovoltaic modules to the building roof substrate and interior, significantly reducing indoor temperature, achieving natural cooling of the house, and reducing energy consumption of air conditioning and other cooling equipment; on the other hand, as the ambient temperature decreases at night, the hydrogel releases the heat stored during the day, restoring to the initial state of phase change, achieving cyclic heat storage and release, and maintaining the thermal insulation effect all day long. In summer, the inner surface temperature of the roof can be reduced by 5-10℃, and the indoor heat gain is reduced by 25%-40%.

[0041] (3) High flame retardant properties class)

[0042] The hydrogel matrix contains a large amount of bound and free water. When exposed to fire, the water evaporates and absorbs heat, while the polymer network forms a dense carbonized layer that isolates oxygen and prevents the spread of flame. The patch achieved the highest flame retardant rating in the UL94 vertical burning test. There are no dripping particles; when photovoltaic modules experience faults such as short circuits, overheating and fire, the hydrogel layer can prevent the flames from spreading downwards to the building roof, while the evaporation of water absorbs heat to further suppress the fire, thus comprehensively improving the fire safety level of photovoltaic roof buildings.

[0043] Preferred feature: self-adhesive

[0044] To overcome the shortcomings of traditional phase change patches that require additional adhesives or other media for fixation, the hydrogel material of this invention preferably employs a molecular structure design strategy: introducing a self-adhesive component into the polymer network. This component forms multiple hydrogen bonds and metal coordination chelates in situ with polar functional groups (such as hydroxyl, amino, or metal oxide sites) on the surface of the building roof substrate and photovoltaic module backsheet. This molten self-adhesion has a reversible response characteristic: the patch can be peeled off or replaced from the substrate surface at any time, facilitating construction positioning, position adjustment, and subsequent maintenance, completely eliminating dependence on external adhesives (adhesion strength). ).

[0045] Preferred features: Crystallization control and rigid interlocking

[0046] To overcome the drawback of traditional phase change patches being prone to detachment during long-term service, the hydrogel patch of this invention preferably employs a fixed material combination design: multiple nucleating agents are added to the inorganic phase change material, precisely controlling the crystallization temperature of the patch between 7 and 35°C. Under normal temperature conditions (such as at night), the patch spontaneously transforms from a soft, self-adhesive molten state to a crystalline state. During crystallization, the volume expands slightly, promoting a mechanical interlock between the patch and the micro-rough surfaces of the building roof substrate and the photovoltaic module backsheet, thus increasing the interfacial adhesion strength from the molten state. Sudden rise to crystalline state This dual fixing mechanism of "molten reversible adhesion - crystalline rigid interlock" realizes the differentiated functional requirements of flexible adjustment during construction and permanent fixation during service. It requires no adhesives or fasteners and ensures that the patch does not slip or warp during long-term thermal cycling service.

[0047] Preferred features: chemical cross-linked network and ultra-long cycle stability

[0048] The phase change material hydrogel patch of this invention adopts a multi-network structure formed by chemical cross-linking (covalent bonds), resulting in a more durable and stable shape and mechanical structure, and permanently encapsulating the phase change material. Compared with physically cross-linked networks, chemically cross-linked networks are structurally stable during repeated melt-crystallization cycles and do not experience fatigue collapse. After 500 accelerated cycle tests, the latent heat retention rate is ≥99%, with no leakage of phase change material, meeting the long-term use requirements of photovoltaic roofs.

[0049] Preparation and installation methods

[0050] Inorganic hydrated salt phase change material, various polymer monomers, self-adhesive components, crosslinking agents, crystallizing nucleating agents, initiators, and water are mixed in a certain proportion, injected into a mold, and polymerized by ultraviolet light irradiation or heating to form a chemically crosslinked hydrogel. Demolding yields a self-adhesive patch. During on-site construction, the patch is directly adhered to the cleaned roof substrate surface in a molten state, followed by the attachment of photovoltaic modules. After standing at an ambient temperature of 7–35℃ for 2–10 hours, the patch spontaneously crystallizes and forms a rigid interlock, completing the integrated installation.

[0051] Beneficial effects of the present invention

[0052] 1. High functional integration: A single hydrogel patch can simultaneously achieve three major functions: photovoltaic cooling, building insulation, and fire retardancy, replacing the traditional multi-layer complex structure and simplifying the structure.

[0053] 2. Significantly improved photovoltaic power generation efficiency: Through high latent heat storage, the module temperature drops by ≥10℃, and the power generation efficiency is relatively improved by ≥8% (actual measurement can reach more than 10%).

[0054] 3. Outstanding building energy-saving effect: Low thermal conductivity effectively blocks heat conduction, reducing indoor heat gain by ≥25% and air conditioning energy consumption by 15% to 25%.

[0055] 4. Fire-resistant and reliable: It is flame retardant to meet building fire protection standards and eliminates fire hazards on photovoltaic roofs.

[0056] 5. Strong and reliable connection: self-adhesive + rigid interlocking with crystallization, no adhesive or fasteners required, will not fall off after 500 cycles.

[0057] 6. For crystalline silicon solar cells (high thermal conductivity): Heat is rapidly conducted from the front to the back, with a temperature difference of less than 1°C between the upper and lower surfaces. The patch layer acts only as a highly efficient passive cooling layer, absorbing and storing heat to reduce the operating temperature of the cell and improve efficiency by 10%. For perovskite solar cells, due to their low thermal conductivity, under illumination, the front side (the light-receiving side) of the cell generates Joule heat, becoming the hot end, while the back side becomes the cold end due to heat absorption by the patch layer. Because the perovskite layer has extremely poor thermal conductivity, this temperature difference cannot be uniformized through heat conduction, thus establishing a vertical temperature gradient along the thickness of the device. This gradient drives carrier migration, generating a thermoelectric potential, which forms a series enhancement with the photogenerated electric field, ultimately achieving "photovoltaic-thermoelectric coupling," not only achieving cooling but also improving efficiency.

[0058] Industrial applicability

[0059] The integrated photovoltaic roof building structure provided by this invention utilizes readily available raw materials and mature manufacturing processes (UV polymerization or thermal polymerization) for its core phase change material, hydrogel patches. These patches can be prefabricated in factories into standard-sized modules for rapid on-site assembly. The patches spontaneously crystallize and interlock at room temperature, requiring no special equipment or skills. A waterproof sealing layer and modular design further enhance the system's practicality and maintainability. It is suitable for new and retrofit projects of various photovoltaic roofs, including residential buildings, industrial plants, public buildings, and agricultural greenhouses, and is particularly suitable for regions with hot summers and cold winters, as well as hot summers and warm winters, offering significant economic and social benefits. Attached Figure Description

[0060] Figure 1 Example 1 shows the performance of the phase change hydrogel prepared in the following figure: a is the differential scanning calorimetry (DSC) cycle curve, b is the cooling curve, and c is the adhesion force curve of the molten state and the crystalline state.

[0061] Figure 2 Example 2: Flame-retardant thermal infrared imaging image of phase change hydrogel.

[0062] Figure 3 Example 4 shows the mass change curves of the phase change hydrogel prepared before and after molding, where a represents before molding and b represents after molding.

[0063] Figure 4 Temperature-time curves of the phase change hydrogel prepared in Example 1 and the hydrogel patch prepared in Example 3 applied to a roof.

[0064] Figure 5 Example 1 shows the cooling performance and temperature monitoring of the phase change material hydrogel integrated into a photovoltaic cell. In the figure, a is a structural composition diagram of the crystalline silicon photovoltaic panel and the phase change hydrogel, b is a monitoring diagram at temperature 1, c is a comparative monitoring diagram of temperature 1, temperature 2 and temperature 3, and d is a diagram of open circuit voltage and current density.

[0065] Figure 6The thermoelectric synergistic performance of the phase change material hydrogel prepared in Example 1 integrated into the perovskite photovoltaic module is shown in the figure. In the figure, a is the composition of the perovskite photovoltaic module, b is the open circuit voltage and current density graph, and c is the efficiency normalization graph.

[0066] Figure 7 Example 1 shows the thermoelectric performance test diagram of the phase change material hydrogel integrated into the perovskite photovoltaic module, where a is the thermoelectric performance test system, b is the circuit diagram, c is the current power diagram, and d is the current voltage diagram.

[0067] Figure 8 : Schematic diagram of the integrated photovoltaic roof building structure of this invention. Detailed Implementation

[0068] Example 1: Take 270g of calcium chloride hexahydrate, 5g of acrylamide, 10g of deionized water, 0.005g of N,N'-methylenebisacrylamide, 0.005g of α-ketoglutaric acid, 0.5g of corn starch, and 2.7g of borax, and mix them thoroughly at 50℃. Pour the mixture into a 200×200mm... 2 The phase change hydrogel sheet was polymerized and cured in a 1.5cm thick mold, and then demolded to obtain a phase change hydrogel sheet. The phase change hydrogel sheet has a melting point of 23.3℃ and a melting enthalpy of 140.7J / g.

[0069] Example 2: Take 270g of disodium hydrogen phosphate dodecahydrate, 5g of acrylic acid, 5g of deionized water, 0.01g of N,N'-methylenebisacrylamide, 0.01g of α-ketoglutaric acid, 0.5g of gelatin, and 8.1g of sodium metasilicate nonahydrate, and stir and mix them evenly at 70℃. Pour the mixture into a 200×200mm... 2 The material is polymerized and cured in a 1.5cm thick mold, and after demolding, a phase change material hydrogel sheet is obtained. The phase change hydrogel sheet has a melting point of 32.2℃ and a melting enthalpy of 210.3J / g.

[0070] Example 3: Take 5g of acrylamide, 10g of deionized water, 0.005g of N,N'-methylenebisacrylamide, 0.005g of α-ketoglutaric acid, 0.5g of corn starch, and 2.7g of borax, and mix them thoroughly at 50℃. Pour the mixture into a 200×200mm... 2 The material is polymerized and cured in a 1.5cm thick mold. After demolding, a hydrogel sheet is obtained, which has no phase change properties.

[0071] Example 4: Take 270g of sodium acetate trihydrate, 5g of sodium acrylate, 10g of deionized water, 0.01g of N,N'-methylenebisacrylamide, 0.005g of potassium persulfate, 0.5g of corn starch, and 2.7g of strontium chloride hexahydrate, and stir and mix them evenly at 60℃. Pour the mixture into a 200×200mm... 2The phase change hydrogel sheet was polymerized and cured in a 1.5cm thick mold, and then demolded to obtain a hydrogel sheet. The melting point of this phase change hydrogel sheet is 57.6℃, and the enthalpy of fusion is 188.9J / g.

[0072] Example 5: Take 270g of calcium chloride hexahydrate, 5g of acrylamide, 10g of deionized water, 0.005g of N,N'-methylenebisacrylamide, 0.005g of α-ketoglutaric acid, and 2.7g of borax, and mix them thoroughly at 50℃. Pour the mixture into a 200×200mm... 2 The material is polymerized and cured in a 1.5cm thick mold. After demolding, a phase change hydrogel sheet is obtained, which is non-self-adhesive.

[0073] like Figure 1 As shown, the phase change hydrogel sheet prepared in Example 1, as tested by DSC, had a melting point of 23.3℃, ​​a melting enthalpy of 140.7 J / g, and a crystallization temperature of 22℃. After 500 heating and cooling cycles (temperature range 0℃~50℃, rate 10℃ / min), the phase change enthalpy retention rate was 99%, the phase change temperature showed no significant drift, and no leakage of the phase change material was observed. This indicates that the material of the present invention has excellent long-term stability. This material possesses a dual fixation mechanism of reversible adhesion in the molten state and rigid interlocking in the crystalline state; the adhesion force in the molten state is 13.6 kPa, which increases sharply to 292 kPa after crystallization. The thermal conductivity of this material was measured to be... .

[0074] like Figure 2 As shown, the phase change material hydrogel sheet (20×20mm², 0.5cm thick) prepared in Example 2 was directly bonded to the back surface of a commercial monocrystalline silicon photovoltaic cell (20×20mm²). The sheet was directly burned with a flame, and infrared thermal imaging showed that the sheet temperature reached 548.7℃ within 30 seconds, while the silicon cell temperature remained within the 27-37℃ range. The photograph shows that the sheet turned black, but the silicon cell remained intact, fully demonstrating the excellent flame-retardant properties of the phase change material hydrogel sheet. The sheet achieved the highest flame-retardant rating in the UL94 vertical burning test. .

[0075] The phase change hydrogel patch prepared according to the method of Example 4 was thermo-encapsulated using a polyethylene terephthalate (PET) encapsulation film. The encapsulated patch was placed in an outdoor natural environment (temperature range -10 to 45°C, humidity 30% to 80% RH), and samples were periodically taken to test its mass change and phase change performance. Experimental results are as follows: Figure 3As shown, without plastic sealing, the phase change hydrogel prepared in Example 4 could not effectively retain moisture, and its weight decreased to 96.5% within 6 hours; while plastic sealing significantly slowed down moisture evaporation. These results indicate that encapsulation with a plastic film can effectively prevent moisture loss from phase change materials, significantly improve the long-term service stability of the patch, and meet the durability requirements of building roofs.

[0076] The phase change hydrogel patch prepared in Example 1 and the ordinary hydrogel patch without phase change material prepared in Example 3 (as a control group) were respectively heat-sealed using polyethylene terephthalate (PET) encapsulation film. Subsequently, the encapsulated patches were laid flat on the roof of a house, and the temperature changes inside the house were continuously monitored. Figure 4 As shown, compared with ordinary hydrogels, phase change hydrogels exhibit excellent temperature retention capabilities, effectively mitigating the fluctuations in indoor temperature caused by external environmental factors, thus providing a significant thermal buffering effect.

[0077] like Figure 5 As shown, a phase change material hydrogel sheet (20×20mm², 1.5cm thick) prepared in Example 1 was directly bonded to the back surface of a commercial monocrystalline silicon photovoltaic cell (20×20mm², initial photoelectric conversion efficiency 13.656%). Testing was conducted under AM1.5G standard illumination (1000W / m²). Temperature was monitored using an infrared thermal imager and a T-type thermocouple, and the JV curve was measured. Results showed: the steady-state temperature of the standard cell was 50.3℃, while the integrated steady-state temperature was 28.2℃, a decrease of 14.9℃; the open-circuit voltage increased from 0.567V to 0.624V; the fill factor increased from 74.19% to 74.65%; and the photoelectric conversion efficiency increased from 13.656% to 15.111%, a relative improvement of 10%.

[0078] like Figure 6 As shown, a hydrogel sheet of phase change material (14×14cm², 1.5cm thick) prepared in Example 1 was bonded to a perovskite photovoltaic module of the same size (structure). The backlight surface contains 14 sub-cells (effective area 102.88 cm²). Testing was conducted under AM1.5G illumination. The standard perovskite module had a light-receiving surface temperature of 50°C and a backlight surface temperature of 46°C, a temperature difference of 4°C. After integration, the light-receiving surface remained at 50°C, while the backlight surface stabilized at 33°C, a temperature difference of 17°C. JV testing showed that the photoelectric conversion efficiency increased from 20.22% to 22.89%, the open-circuit voltage increased by 0.278V, and the short-circuit current density increased. A 1000-hour stability test showed that even with the addition of phase change material, the efficiency remained at 90%.

[0079] like Figure 7The test circuit diagram is shown in the figure. The resistance of the resistance box is measured using an ohmmeter, according to the formula I=U. 负载 / R 负载 The loop current was calculated. Under dark conditions, the hot-end temperature was maintained at approximately 50°C, and the cold-end temperature was kept constant at approximately 33°C by applying a phase change material. Under these conditions, the external load resistance was varied (starting from 5kΩ and increasing in 5kΩ increments up to 50kΩ), and the output current, output voltage, and output power were measured. The temperature difference was further increased: the hot-end temperature was stabilized at approximately 90°C, and the cold-end temperature at 43°C. The external load resistance was again varied (5–50kΩ, in 5kΩ increments), and the output electrical parameters were measured. The results show that even in the dark condition with only a temperature difference, the photovoltaic cell can still generate voltage and current output, indicating that thermoelectric output can be generated when a longitudinal temperature difference exists. During continuous testing at the maximum power point for 1000 s, the output voltage remained constant at 50μV. Although the thermoelectric output is smaller than the photoelectric output, the thermoelectric field and photoelectric field synergistically enhance each other, further promoting carrier transport and collection, thus forming an overall photoelectric-thermoelectric synergistic amplification effect and improving the final output power.

Claims

1. A photovoltaic roof integrated building structure that combines cooling, heat insulation, flame retardancy, and power generation efficiency enhancement functions, characterized in that: The photovoltaic roof integrated building structure includes a building roof substrate, encapsulated phase change material hydrogel functional patches, and photovoltaic modules; The encapsulated phase change material hydrogel functional patch is sandwiched between the building roof substrate and the photovoltaic module, and the three are stacked and fixed from top to bottom; all side surfaces of the encapsulated phase change material hydrogel functional patch exposed to the environment are provided with a waterproof vapor encapsulation layer to prevent internal moisture evaporation from causing phase change and failure. The encapsulated phase change material hydrogel functional patch is composed of a multi-network skeleton constructed by combining fixed materials. The composition includes the following components, which are chemically cross-linked: inorganic hydrated salt phase change material, self-adhesive material, polymer monomer or polymer skeleton, crystallizing nucleating agent, cross-linking agent, and water. With this fixed material combination, the encapsulated phase change material hydrogel functional patch can spontaneously crystallize below the material crystallization temperature and generate micro-volume expansion, forming a rigid interlock with the contact surface of the building roof substrate and photovoltaic module, thereby enhancing adhesion. A multi-network skeleton contributes to achieving durable and stable mechanical properties.

2. The photovoltaic roof integrated building structure according to claim 1, characterized in that: The encapsulated phase change material hydrogel functional patch has the following basic characteristics: (a) High latent heat: latent heat of phase transition The phase transition temperature range is 18–60℃; (b) Low thermal conductivity: thermal conductivity at room temperature ; (c) High flame retardancy: The flame retardancy rating reaches class; It absorbs heat from photovoltaic modules during the day to undergo a phase change and melt, thereby reducing the temperature of the photovoltaic modules. At night, it releases heat and crystallizes back to its original state, and throughout the process, it has the ability to be self-adhesive, block heat conduction, and prevent the spread of flames.

3. The photovoltaic roof integrated building structure according to claim 1, characterized in that: The building roof base can be any one of the following: concrete roof, asphalt roof, waterproof membrane roof, wood structure roof, thermal insulation board roof, or steel structure roof.

4. The photovoltaic roof integrated building structure according to claim 1, characterized in that: The photovoltaic module is any one of crystalline silicon photovoltaic panels, thin-film photovoltaic panels, double-glass photovoltaic panels, flexible photovoltaic panels, and other new types of photovoltaic modules; The crystalline silicon in the crystalline silicon photovoltaic panel has high thermal conductivity, which absorbs solar heat and conducts it rapidly from the front to the back of the crystalline silicon photovoltaic panel. The temperature difference between the upper and lower surfaces of the crystalline silicon photovoltaic panel is less than 1°C. The encapsulated phase change material hydrogel functional patch absorbs and stores heat, and only serves as a passive cooling layer to reduce the operating temperature of the crystalline silicon photovoltaic panel. In the perovskite solar cells of the aforementioned thin-film photovoltaic panel, the ultra-low thermal conductivity of the perovskite material allows for the active construction and maintenance of a vertical temperature difference through localized cooling on the back surface without damaging the perovskite solar cell structure. This temperature gradient is converted into a thermoelectric field, which, in conjunction with the photogenerated electric field, utilizes its low thermal conductivity in a reverse-thinking manner. Under illumination, the front of the perovskite solar cell generates Joule heat, becoming the hot end, while the back end absorbs heat due to the encapsulated phase change material hydrogel functional patch, becoming the cold end. Because the perovskite layer has extremely poor thermal conductivity, this temperature difference cannot be homogenized through heat conduction, thus establishing a vertical temperature gradient in the thickness direction of the device. This vertical temperature gradient drives carrier migration, generating a thermoelectric potential, which forms a series enhancement with the photogenerated electric field, ultimately achieving "photovoltaic-thermoelectric coupling".

5. The photovoltaic roof integrated building structure according to claim 1, characterized in that: The encapsulated phase change material hydrogel functional patch features a flexible, monolithic or modular design, with each photovoltaic module corresponding to a single encapsulated phase change material hydrogel functional patch, facilitating future inspection, replacement, and maintenance; the patch thickness is... The selection should be based on the climate conditions of the building's location, the roof orientation, and the power of the photovoltaic modules.

6. The photovoltaic roof integrated building structure according to claim 1, characterized in that, The preparation method of the encapsulated phase change material hydrogel functional patch includes the following steps: (1) Inorganic hydrated salt phase change material, self-adhesive material, various polymer monomers or polymer skeletons, crosslinking agent, crystallizing nucleating agent, initiator and water are mixed in proportion and injected into a mold. The shape can be adjusted arbitrarily according to the mold and can be prepared on a large scale. (2) The polymer monomers and crosslinking agents form a chemically crosslinked multi-network structure by ultraviolet light irradiation or thermal polymerization; (3) Demolding to obtain a self-adhesive phase change material hydrogel functional patch; (4) Add a waterproof vapor encapsulation layer to all side surfaces of the phase change material hydrogel functional patch exposed to the environment, directly attach the encapsulated phase change material hydrogel functional patch to the upper surface of the building roof substrate, and then attach the photovoltaic module. Let it stand for 2-10 hours in an environment lower than the crystallization temperature of the encapsulated phase change material hydrogel functional patch, or by local cooling, so that the encapsulated phase change material hydrogel functional patch spontaneously crystallizes and forms a rigid interlock with the upper and lower surfaces.

7. The photovoltaic roof integrated building structure according to claim 1, wherein the encapsulated phase change material hydrogel functional patch is characterized in that: In the molten state, it is transparent in color. The encapsulated phase change material hydrogel functional patch has self-adhesion and strong adhesion. Shear deformation It can perfectly fit photovoltaic modules; in its crystalline state, it is milky white, and the encapsulated phase change material hydrogel functional patch transforms into a rigid material with increased adhesion strength. It forms a mechanical interlock with the micro-rough structure of photovoltaic modules and building roof substrate through the micro-expansion of volume during the crystallization process; the presence state of the encapsulated phase change material hydrogel functional patch can also be judged by the color change; after more than 500 melting-crystallization cycles, the latent heat retention rate of phase change is ≥99%, and there is no leakage.

8. The photovoltaic roof integrated building structure according to claim 6, characterized in that: The inorganic hydrated salt phase change material is selected from any one or more of sodium sulfate decahydrate, sodium carbonate decahydrate, disodium hydrogen phosphate dodecahydrate, calcium chloride hexahydrate, zinc nitrate hexahydrate, sodium thiosulfate pentahydrate, and sodium acetate trihydrate. The phase change temperature can also be adjusted to the range of 18-38℃ through eutectic. The nucleating agent is selected from any one or more of borax, cesium chloride hexahydrate, strontium chloride hexahydrate, sodium metasilicate nonahydrate, nano-silica, nano-alumina, and graphene quantum dots. The amount of nucleating agent added is 0.01% to 15% of the mass of the inorganic hydrated salt phase change material. The polymer backbone is a network backbone chemically cross-linked with polymer monomers; the polymer backbone is selected from any one or more of polyacrylamide, polyacrylic acid, sodium polyacrylate, polymethacrylic acid, sodium polymethacrylate, polyN-isopropylacrylamide, poly2-acrylamido-2-methylpropanesulfonic acid, polyvinylpyrrolidone, polyvinyl alcohol, polydimethyldiallyl ammonium chloride, and sodium alginate; the amount of polymer monomer added is 0.5% to 10% of the mass of the inorganic hydrated salt phase change material; The self-adhesive material is selected from any one or more of the following: dopamine methacrylamide, gelatin, gallic acid, protocatechuic aldehyde, tannic acid, poly-N-isopropylacrylamide, hyaluronic acid, chitosan and its derivatives, corn starch, and carboxybetaine; the amount of self-adhesive material added is 0.01% to 20% of the mass of the inorganic hydrated salt phase change material.

9. The photovoltaic roof integrated building structure according to claim 6, characterized in that: The crosslinking agent is selected from any one or more of N,N'-methylenebisacrylamide, dimethyl diallyl ammonium chloride, and glutaraldehyde; the amount of crosslinking agent added is 0.0001% to 0.01% of the mass of the inorganic hydrated salt phase change material.

10. The photovoltaic roof integrated building structure according to claim 6, characterized in that: The initiator is selected from any one or more of α-ketoglutaric acid, ammonium persulfate, potassium persulfate, and azobisisobutyramidine hydrochloride; the amount of initiator added is 0.0001% to 0.01% of the mass of the inorganic hydrated salt phase change material.